Cardio-ankle Velocity Index (CAVI) as a Marker of Multivessel Coronary Artery Disease in Diabetic Patient - Talib, Ali Abdulkarim (International Journal of Psychosocial Rehabilitation, 2020)
Aim: To investigate the ability of the arterial stiffness parameter cardio-ankle velocity index (CAVI) to predict coronary disease in diabetic patient. Method: 155 consecutive patients underwent CAVI prior for coronary angiography for different indications between March 2018 until March 2019 at Al Hussein teaching hospital-Samawah city-Iraq. Patients with atrial fibrillation, aortic valve regurgitation and low Ankle Brachial Index (ABI<0.9) were excluded. After coronary angiography, patients were categorized as those with no vessel disease (group 1), those with single vessel disease (1VD) (group 2), those with two vessels disease (2VDs) (group 3) and those with three vessels disease (3VDs) (group4). In relation to diabetes they were categorized into four groups: Those has no DM and No demonstrable CAD (Non DM. Non CAD) (group 1), those with no DM but CAD (Non DM. CAD) (group2), Those with DM and no CAD (DM. NonCAD) (group 3) and those DM and CAD (DM.CAD) (group 4). Results: CAVI was significantly higher in those with 1VD than normal (mean±SD) (9.35±1.05 Vs 8.138±6.73) (P<0.05), Those with 2VD has significantly higher CAVI than those with no vessel disease (mean±SD) (9.8±0.84 Vs 8.13±6.73) (P<0.05), Those with 3VD has significantly higher CAVI than those with No vessel disease (mean±SD) (11.48±1.1 Vs 8.138±6.73), (P<0.001) Those with 3VDS has significantly higher CAVI than those with 2VD (mean±SD) (11.48±1.1 Vs 9.8±0.84) (P<0.05). As for Diabetics, Those with DM and CAD (group 4) has the highest CAVI among other groups (mean±SD) (10.73 ±1.323 Vs 9.865±1.346) (p<0.05). Conclusion: CAVI can be a simple non-invasive test to predict multivessel disease in diabetic patients.